Occupational exposure to HIV and use of post-exposure prophylaxis in a general hospital in North Central, Nigeria. - Olaleye, Abiola O; Ogundele, Olorunfemi A; Awokola, Babatunde I; Olatunya, Oladele S; Olaleye, Omolara A; Adeyanju, Titilope; Omisore, Akinlolu G (International Journal of Occupational Safety and Health, 2013)
Occupational exposures to blood borne pathogens including HIV have been well studied. However, limited studies exist about the utilization of post exposure prophylaxis and follow-up in Nigeria. The objectives of the study were to describe the characteristics of occupational exposure to HIV, the utilization of post exposure prophylaxis (PEP) among health workers, and the proportion of exposed health workers reporting for follow-up three months after exposure. A cross sectional descriptive study involving ninety three health workers was carried out at a general hospital located in an urban area in North Central zone of Nigeria. A simple random sampling technique was used. The prevalence of occupational exposure, utilization of post exposure prophylaxis and follow-up rate were assessed using self administered questionnaire. Data analysis was done using SPSS version 16 and descriptive analysis was carried out. It was reported that, 73.1% of respondents at least one or more occupational exposures to HIV and other blood borne pathogens through accidental needle injury/prick, blood splash on a fresh wound or conjunctiva exposure in the last one year. Needle stick injury occurred in 83.8% of all respondents who had occupational exposures. 8.8% of exposed respondents commenced post exposure prophylaxis with two-thirds completing the post exposure prophylaxis regimen. Only one (25%) of those who completed the regimen reported for follow-up. Occupational exposures to HIV are common among health workers. The rates of utilization of post exposure prophylaxis and follow-up were low. DOI: http://dx.doi.org/10.3126/ijosh.v3i1.6635 International Journal of Occupational Safety and Health, Vol 3 No 1 (2013) 11-17